Conspiracism on the Runet: Text Reuse and the Formation of a Conspiracy Theory - Oivo, Teemu; Oiva, Mila; Ristilä, Anna (Carleton University, 2026)
While repetition is widely recognized as a key mechanism in shaping cultural knowledge, its role in the formation of misinformation and conspiracy theories remains underexplored. This article examines Russian conspiracism by investigating the role of text reuse in the formation and dissemination of a conspiracy theory within text-based media. Drawing on a corpus of Russian-language websites and newspapers, we identify a prominent cluster that repeatedly promotes claims about an ancient Russian civilization and a multi-generational cover-up. Using a mixed-methods approach, we contextualize these websites and analyze their life cycles, loose interconnectedness, and “patriotic” profiles. The conspiracy theory examined in this case study circulated exclusively online, with the digital environment of the Runet accelerating its diffusion and entrenchment. Our findings of text reuse highlight the salience of lead-in introductions in shaping and reinforcing these narratives.